The image processing handbook - Russ, John C. (Boca Raton : CRC Press, 2011)
'This guide clearly explains the acquisition and use of digital images in a wide variety of scientific fields. This sixth edition features new sections on selecting a camera with resolution appropriate for use on light microscopes, on the ability of current cameras to capture raw images with high dynamic range, and on imaging in more than two dimensions. It discusses Dmax for X-ray images and combining images with different exposure settings to further extend the dynamic range. This edition also includes a new chapter on shape measurements, a review of new developments in image file searching, and a wide range of new examples and diagrams'--
Includes bibliographical references (p. 817-838) and index.
Keywords: Food -- Analysis; Microscopy; Image analysis; TECHNOLOGY & ENGINEERING / Imaging Systems; MEDICAL / Biotechnology